Impairment of exocytotic transmitter release by decynium-22 through an inhibition of ion channels - Haar, Gabriele; Hrachova, Katsiaryna; Wagner, Tanja; Boehm, Stefan; Schicker, Klaus (Frontiers in Pharmacology, 2023)
In addition to members of the family of Na+/Cl- dependent monoamine transporters, organic cation transporters (OCTs), in particular OCT3, as well as the plasma membrane monoamine transporter (PMAT) may contribute to neuronal reuptake of according neurotransmitters. As opposed to the numerous blockers of monoamine transporters, only a very limited number of specific blockers of OCT3 and PMAT are available. In fact, decynium-22 is the only blocking agent with micromolar affinities for both transport proteins, and this molecule is frequently used to establish roles of OCT3 and/or PMAT as targets for antidepressant drugs and psychostimulants, respectively. To test for a function of these transporters in the sympathetic nervous system, uptake and release of [3H]1-methyl-4-phenylpyridinium (MPP+) was investigated in primary cultures of rat superior cervical ganglia. Uptake was reduced by cocaine or desipramine, blockers of the noradrenaline transporter, by about 70% and by corticosterone or β-estradiol, blockers of OCT3, by about 30%; decynium-22 achieved complete inhibition of uptake with half maximal effects at 3 µM. Depolarization dependent release was enhanced by corticosterone or β-estradiol, but reduced by decynium-22. As the latter effect is unlikely to be related to actions at OCT3 and/or PMAT, electrophysiological recordings were performed to reveal that decynium-22 inhibits action potential firing and currents through voltage activated calcium channels in superior cervical ganglion neurons. These results demonstrate that decynium-22 can impair exocytotic neurotransmitter release by interfering with several types of ion channels. Such transporter-independent effects of decynium-22 that my interfere with basic neuronal functions need to be considered when interpreting results obtained with decynium-22 as prototypic inhibitor of transmitter reuptake via OCT3 and/or PMAT.